High Expression MicroRNA-206 Inhibits the Growth of Tumor Cells in Human Malignant Fibrous Histiocytoma - Li, Dejian; Zhao, Kai; Zhao, Ziwen; Jiang, Bo; Gong, Xianxu; Zhang, Yan; Guo, Yingqi; Xiao, Han; Wang, Ye; Liu, Hui; Yi, Chengqing; Gu, Wenguang (Frontiers in Cell and Developmental Biology, 2021)
Background: Malignant fibrous histiocytoma (MFH) is a common type of soft tissue sarcoma and a serious threat to human health. MFH often relapse locally after the curettage is related to the residual cancer stem cells (CSCs). Currently, the dysregulation of microRNA (miRNA) has been found to be closely related to the recurrence of CSCs. However, whether there are dysregulations of miRNAs exist in MFH CSCs remained unkonw. Methods: In this study, micRNAs in MFH CSCs and MFH common cells were examined by gene probe. Then target genes and their functions involved in the signal pathway were predicted by the relevant database. Finally, the miRNAs' target regulatory network was constructed. Furthermore, the miRNAs and target genes were identified by qPCR, while miRNA analogues and antagonists were transfected in tumor cells to further investigate cell proliferation ability. Results: Resultes showed that a total of 47 miRNAs were found, including 16 were up-regulated and 31 down-regulated. The screened differential miRNA showed a different expression in the cell resistant strains compared with the control group. qPCR analysis confirmed that the relative abundance of 7 miRNA and 4 target genes varied significantly. The encouraging issue is that we found Hsa-miR-206 significantly inhibited MFH proliferative activity. Conclusion: Hsa-miR-206 played a key role in regulating MFH CSCs properties which might be a represent marker and target for the diagnosis and treatment of MFH in the future.